Math, asked by danialkul, 11 months ago

please see the attachment ☝️☝️​

Attachments:

Answers

Answered by Anonymous
2

Question

(  \bf \: \csc(A)  -  \sin(A) )( \sec(A)  -  \cos(A) )( \tan(A)  +  \cot(A) )  = 1

Solution:-

(  \bf \: \csc(A)  -  \sin(A) )( \sec(A)  -  \cos(A) )( \tan(A)  +  \cot(A) )  = 1

By Using this trigonometry identities

 \to \:  \csc(A)  =  \frac{1}{ \sin(A) }

 \to  \sec(A)  =  \frac{1}{ \cos(A) }

 \to \:  \tan(A)  =  \frac{ \sin(A) }{ \cos(A) }

 \to \:  \cot(A)  =  \frac{ \cos(A) }{ \sin(A) }

We get

(  \bf \:  \frac{1}{ \sin(A) }   -  \sin(A) )(  \frac{1}{ \cos(A) }  -  \cos(A) )(  \frac{ \sin(A) }{ \cos(A) }   +   \frac{  \cos(A)  }{ \sin(A) } )

Taking lcm we get

 \bf \: ( \frac{1 -  \sin {}^{2} (A) }{ \sin(A) } )( \frac{1 -  \cos {}^{2} (A) }{ \cos(A) } )( \frac{ \sin {}^{2} (A) +  \cos {}^{2} (A)  }{ \sin(A) \cos(A)  } )

Use this trigonometry identities

=> sin²(A) + cos²(A) = 1

=> sin²(A) = 1 - cos²(A)

=> cos²(A) = 1 - sin²(A)

 \bf \: ( \frac{ \cos {}^{2} (A) }{ \sin(A) } )( \frac{ \sin {}^{2} (A) }{ \cos {}^{} (A) } )( \frac{1}{ \sin(A) \cos(A)  } )

\bf \: ( \frac{  \not\cos {}^{ \not2} (A) }{ \sin(A) } )( \frac{ \sin {}^{2} (A) }{  \not{\cos }{}^{} (A) } )( \frac{1}{ \sin(A)  \not\cos(A)  } )

 \bf \:  \frac{ \not \sin {}^{2} (A) }{  \not\sin(A) }  \times  \frac{1}{  \not\sin(A) }

 \implies \: 1

 \bf \: { \red{hence \: proved}}

Similar questions